Do We Have Free Will, or Is Everything Predetermined? A Neuroethics Dilemma - Guerreiro, João (Journal of NeuroPhilosophy, 2025)
The debate over free will and determinism remains one of the most profound philosophical and scientific dilemmas, raising questions regarding human agency, morality, and responsibility. Determinism posits that all actions are dictated by prior causes and natural laws, leaving no room for genuine choice. In contrast, libertarianism argues that humans possess free will, enabling them to act independently of deterministic constraints. Neuroscientific studies, such as Benjamin Libet’s experiments on readiness potential and fMRI research predicting motor intentions, seem to support determinism by suggesting that unconscious brain activity precedes conscious decision-making. However, critics argue that these studies oversimplify free will by focusing on basic motor actions rather than complex cognitive processes. Furthermore, research on intentional inhibition and the ability to consciously override pre-programmed actions challenges deterministic interpretations, suggesting a role for conscious agency. While neuroscience provides valuable insights, the complexity of human thought extends beyond simple movement-based experiments. This paper explores the intersection of philosophy and neuroscience, emphasizing the need for a more nuanced understanding of free will that accounts for higher-order reasoning and moral decision-making.